Mayatyphlus carltoni Gusarov, a new genus and species of leptotyphline staphylinid beetle from Belize (Coleoptera: Staphylinidae: Leptotyphlinae) - Gusarov, Vladimir I. (Zootaxa, 2003)
Mayatyphlus carltoni Gusarov, gen. n. and sp. n. of the tribe Neotyphlini is described from Belize. Diagnostic characters and illustrations are provided to distinguish Mayatyphlus from closely related genera.